Current Approaches to Alkyl Levulinates via Efficient Valorization of Biomass Derivatives - Liu, Xiaofang; Yang, Wenjia; Zhang, Qiuyun; Li, Can; Wu, Hongguo (Frontiers in Chemistry, 2020)
Biomass is a potential non-food, carbon-neutral, and abundant resource, which can be used as an alternative to fossil fuels during the sustainable preparation of various platform chemicals. Alkyl levulinates (ALs) have found widespread application as flavorings, plasticizing agents, and fuel additives, as well as synthetic precursors to various building blocks. Several processes have been investigated to transform biomass and its derivatives into ALs, which mainly include: (i) direct esterification of levulinic acid (LA) with alkyl alcohols and (ii) alcoholysis reactions of renewable biomass feedstocks and their derivatives, including furfuryl alcohol (FAL), chloromethyl furfural (CMF), and saccharides. This review focuses on illustrating the effects of the biomass pretreatment step, catalyst texture, possible mechanisms, acidities, and intermediates on the synthesis of ALs from sustainable resources covering a wide range of intermediates, including diethyl ether (DEE), 4,5,5-triethoxypentan-2-one (TEP), ethoxymethylfuran (EMF), ethyl-D-fructofuranoside (EDFF), and ethyl-D-glucopyranoside (EDGP).